2022
DOI: 10.7759/cureus.30370
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Knowledge and Skills Related to Up-to-Date Implant Techniques Among Prosthodontists, Periodontists, and Oral Surgeons: A Cross-Sectional Study

Abstract: BackgroundA dental implant is used in the treatment of complete and partial edentulism. Implant application has increased significantly in modern dentistry. The anatomy, medical condition, practitioner knowledge, and surgical technique are key factors that eventually affect the overall outcome of dental implants. For a better treatment outcome for dental implants, adequate multidisciplinary communication, cooperation, and support must be achieved while considering the periodontics, prosthodontics, and oral sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Furthermore, when the oral cavity before each surgery is also rinsed with an antiseptic solution, it also improves later outcomes. Any potential inflammation present in the oral cavity influences future dental implant healing [14][15][16][17][18]. Each clinician should carefully plan a step-by-step treatment protocol.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, when the oral cavity before each surgery is also rinsed with an antiseptic solution, it also improves later outcomes. Any potential inflammation present in the oral cavity influences future dental implant healing [14][15][16][17][18]. Each clinician should carefully plan a step-by-step treatment protocol.…”
Section: Discussionmentioning
confidence: 99%
“…This can be achieved by various methods and mostly is related to properly scheduled dental treatment consisting of conservative, periodontal, surgical, and other related procedures to improve the dental status of each patient. It is already known and widely established that any bone surgery in the jaw bones should be scheduled when no active source of inflammation is present in the oral cavity [15][16][17][18][19][20][21][22][23]. This situation is also quite important, because, if teeth are not free of plaque and bacteria, or even the same can be associated with inappropriately endodontic treated teeth, whose poor dental status might promote inflammation in the operating field and might cause the necessity of secondary surgery close to the operated site and cause even more possible serious damage to the nerve located in such close proximity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, no study was conducted to evaluate the factors that affect the choice of an implant specialist among the population. A previous study in Saudi Arabia reported that each dental specialty had its own treatment plan for dental implant placement, with significant knowledge observed in each specialty [ 10 ]. A patient's selection of an implant specialist for placing dental implants can demonstrate a different opinion between each patient; this can be due to several factors, such as cost, social media, dentist qualification, and previous patient experience.…”
Section: Introductionmentioning
confidence: 99%